IMPROVING THE ECONOMY OF SHARIA ECONOMIC COMMUNITY (MES) THROUGH THE “MAPARO GOAT LIVESTOCK” SYSTEM IN ERA 4.0 - Rosidah, Muallifatur (Fakultas Ekonomi dan Bisnis Islam, 2021)
Goat Farming Maparo System in Improving Community Economy. Sadabumi Village, Majenang District, Cilacap Regency, there is a mudharabah collaboration called maparo, maparo is one of the livestock business systems, where farmers do business with capital owners. People who have capital will invest in the form of goats, where later when the goats are adults then they are sold, and the proceeds from the sale will be shared with the owners of capital. This research was conducted in Sadabumi Village, Majenang, Cilacap. Where researchers go directly to the field to research, then the results of the research are in the form of descriptions in the field. In collecting data, researchers used three techniques, namely, observation, interviews and documentation. From the data and information obtained by researchers in the field, the results show that the business with the maparo system that is carried out includes mudharabah muqayyadah. Maparo is not only carried out as a business, but there are other purposes or purposes, including as one of the ways used to establish brotherly relations. Maparo is an alternative to invest for people who have capital, and become an additional job to increase income for people who raise livestock. Maparo business system is also one of the business development systems for capital owners. The mudharabah muqayyadah contract in the maparo system is a manifestation of the principles in sharia business, this is because the purpose of capital in this business is mutual help, fairness in terms of profit sharing, and the principle of sharing risks in losses that occur during the business. While other results found in the field, namely, maparo male goats are more profitable than female goats